The Total Thrombus Formation (T-TAS) platelet (PL) assay, a novel test that evaluates whole blood platelet thrombus formation under physiological conditions. (17th February 2022) - Zheng, K.L.; Wallen, H.; Aradi, D.; Godschalk, T.C.; Hackeng, C.M.; Dahlen, J.R.; Ten Berg, J.M.
Abstract: Dual antiplatelet therapy (DAPT, aspirin, and a P2Y12 inhibitor) reduces thrombotic events in patients with coronary artery disease (CAD). The T-TAS PL assay uses arterial shear flow over collagen surface, better mimicking in vivo conditions compared to conventional agonist-based platelet function assays, to evaluate platelet function. Here, the platelet function in patients taking DAPT is evaluated with the T-TAS PL assay. In 57 patients with CAD, taking DAPT ≥7 days (n = 22 for clopidogrel, n = 15 for prasugrel, n = 20 for ticagrelor), T-TAS PL assessments were performed in duplicate, and expressed as area under the flow pressure curve within a 10-minute period (AUC10). The duplicate measurements were strongly correlated (r = 0.90, p < .001), with an intra-assay coefficient of variation (CV) of 11, 5%. For clopidogrel, the median AUC10 was 11.5 (IQR5.9–41.8), for prasugrel 28.8 (IQR10.3–37.6), and for ticagrelor 8.9 (IQR 6.4–10.9). All measurements were below the AUC10 cutoff of 260 measured in healthy volunteers, suggesting excellent discrimination of DAPT-treated and untreated persons. The new T-TAS PL assay demonstrated complete discrimination of platelet function in patients on DAPT based on an established cutoff. Ticagrelor showed lower levels of platelet function and a more uniform response compared to prasugrel and clopidogrel.